2023
DOI: 10.1111/imr.13255
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation chimeric antigen receptors for T‐ and natural killer‐cell therapies against cancer

Ye Li,
Katayoun Rezvani,
Hind Rafei

Abstract: SummaryAdoptive cellular therapy using chimeric antigen receptor (CAR) T cells has led to a paradigm shift in the treatment of various hematologic malignancies. However, the broad application of this approach for myeloid malignancies and solid cancers has been limited by the paucity and heterogeneity of target antigen expression, and lack of bona fide tumor‐specific antigens that can be targeted without cross‐reactivity against normal tissues. This may lead to unwanted on‐target off‐tumor toxicities that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 177 publications
(322 reference statements)
0
7
0
Order By: Relevance
“…An important extratumoral effect of CAR-T-cell therapy is trogocytosis, which consists of receptor-mediated transfer of cognate antigen from tumor cells to immune cells expressing the receptor [ 158 ]. This results in loss of antigen and promotes tumor escape from CAR-T cell therapy [ 134 ]. Tumor antigen escape is the main reason of developing resistance to CAR-T cell therapy [ 134 , 158 , 159 ].…”
Section: The Cancer Immunotherapy Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An important extratumoral effect of CAR-T-cell therapy is trogocytosis, which consists of receptor-mediated transfer of cognate antigen from tumor cells to immune cells expressing the receptor [ 158 ]. This results in loss of antigen and promotes tumor escape from CAR-T cell therapy [ 134 ]. Tumor antigen escape is the main reason of developing resistance to CAR-T cell therapy [ 134 , 158 , 159 ].…”
Section: The Cancer Immunotherapy Strategiesmentioning
confidence: 99%
“…This results in loss of antigen and promotes tumor escape from CAR-T cell therapy [ 134 ]. Tumor antigen escape is the main reason of developing resistance to CAR-T cell therapy [ 134 , 158 , 159 ].…”
Section: The Cancer Immunotherapy Strategiesmentioning
confidence: 99%
“…Interestingly, the foundational CAR design also works in NK cells. In the review by Rezvani and colleagues, 11 they highlight advances and understanding in CAR T and NK cells. Recent clinical trials with CAR NK cells have demonstrated exciting clinical efficacy with fewer side effects than CAR T cells.…”
Section: Beyond Conventional T Cellsmentioning
confidence: 99%
“…However, these come at a high treatment cost and can be associated with severe toxicities. NK cells are under clinical assessment for solid and haematological malignancies in multiple phases 1 and 2 trials as an alternative cellular source for CAR-based therapies ( Table 2 ) [ 45 , 62 ]. Importantly, CAR-NK cells have the potential for off-the-shelf utility (allowing for reduced product cost and time) and reduced toxicities compared to CAR-T therapy (reviewed in [ 45 , 63 , 64 ]).…”
Section: Car-nk Cellsmentioning
confidence: 99%